Measuring Persistence on Consumption in Portugal - Belbute, José (2012)
The paper deals with the detection and measurement of the level of persistence on aggregate private consumption in Portugal, USA, European Union and EuroZone as well as on some categories of aggregate consumption in Portugal. By the use of a non-parametric methodology applied to monthly data (1992-2007) it is concluded that aggregate consumption in Europe (both European Union and Euro Zone) is more persistent than in the USA and in Portugal. In particular, the relatively lower degree of persistence shown by the consumption in Portugal can be beneficial for the effectiveness of the countercyclical fiscal and monetary policies that are currently being implemented to overcome the current economic crisis. Our results also suggest that consumption of durables is less persistent, also being more volatile. This result is important in the explanation of the severity of the current economic crisis in Portugal.